PENDAMPINGAN PENGEMBANGAN BAHAN AJAR BERBASIS TEKNOLOGI UNTUK ANAK USIA DINI BAGI GURU PAUD KECAMATAN CURUG KOTA SERANG PROPINSI BANTEN - Fuja Siti Fujiawati; Reza Mauldy Raharja; Atep Iman (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2023)
The development of technology-based teaching materials is one of the competencies that teachers must have in dealing with technological developments in the digital era, coupled with the current pandemic conditions, teachers are forced to develop online-based learning including learning for early childhood. As a professional Early Childhood Education teacher, of course, you must have competence in developing technology-based teaching materials, but in the implementation of Early Childhood Education, there are still many educators who do not have this ability because there are still many PAUD teachers who have not received Early Childhood Education. For example, in Curug subdistrict, which is located not far from the government center, which has 55 Early Childhood Schools, and only two Kindergarten schools have State status, the rest are “SPS” study groups that are voluntarily managed by the community. Departing from these problems, the community service planning program which aims to assist in the development of technology-based teaching materials for early childhood to early childhood teachers in Curug District, Serang City, Banten. This community service activity is carried out with online workshops and mentoring for PAUD teachers to be able to make technology-based teaching materials in a simple form through learning videos tailored to the needs of a pandemic like today The mentoring activity was carried out for one month, and the results obtained from this activity were that early childhood teachers were able to make teaching materials in the form of learning videos that could be used to help the learning process from home during this pandemic.